Using deadlifts as a postactivation performance enhancement strategy in warm-ups in football - Abade, E.; Brito, J.; Gonçalves, B.; Saura, L.; Coutinho, D.; Sampaio, J. (The Journal of Strength and Conditioning Research, 2023)
Postactivation performance enhancement activities may be relevant warm-up strategies aiming to improve subsequent physical performance. The purpose of the current study was to investigate the effects of adding barbell deadlift or hex-bar deadlift exercises to current warm-up routines on running and jumping performances in football players. Ten highly trained male football players participated in the study during the competitive phase of the season. All players performed 3 protocols in the same week: a standard warm-up that included players' regular routines and 2 other protocols with the addition of barbell or hex-bar deadlift, after the end of the warm-up (3 sets of 3 reps, progressing set by set from 60% to 85% repetition maximum). All protocols had the same time interval between pretest (immediately after the warm-up) and posttest (15 minutes after the warm-up). Vertical jumping (countermovement jump [CMJ]; Abalakov jump [AJ]) and running performances (505 test) were impaired 15 minutes after the standard warm-up (CMJ: -6.7 ± 4.2%; AJ: -8.1 ± 8.4%; and 505 time: 1.4 ± 2.5%). For warm-up with the addition of barbell deadlift, vertical jump increased by 4.3 ± 5.6% (Cohen's dunb: 0.23 [0.02-0.47]) and 505 time decreased by -5.9 ± 3.6% (Cohen's dunb: 0.97 [-1.68 to -0.43]). The warm-up with hex-bar deadlift led to trivial changes for CMJ and AJ, but 505 time decrease by -2.7 ± 2.6% (Cohen's dunb: -0.53 [-1.01 to -0.13]). The deadlift exercise can be added to warm-up routines to maintain or even enhance acute physical performance. However, coaches and practitioners should be aware that performance enhancements resultant from deadlift may vary according to individual physical profiles.